A cross-sectional study on the mediating role of psychological capital in the relationship between workplace violence and professional commitment among nursing students - Cai, Zhengrong; Jiao, Lili; Huang, JinJing; Peng, Cui; Chen, AiLing; Shen, ZhouMin; Liu, Yan (Frontiers in Public Health, 2025)
BackgroundStudies have documented associations among workplace violence (WPV), psychological capital (PsyCap), and professional commitment (PC). But limited research has investigated how PsyCap mediates the relationship between WPV and PC, particularly among nursing interns.ObjectiveThis study assessed the current status of WPV, PsyCap, and PC among Chinese nursing students, analyzed thier interrelationships and further determined whether PsyCap mediated the association between WPV and PC.MethodsA cross-sectional survey of 520 nursing interns used validated instruments: a demographic questionnaire, the WPV Scale, the PC Scale, and the PsyCap Questionnaire (Chinese version of PCQ). Pearson correlation analyzed the relationships among PsyCap, WPV, and PC, while hierarchical regression tested the mediation model.ResultsThe total scores for PC and PsyCap among nursing students were (77.04 ± 17.04) and (91.90 ± 16.16), respectively. Approximately 31.54% of the participants reported experiencing WPV. PsyCap was inversely associated with WPV (r = −0.619, p = 0.024) and positively associated with PC (r = 0.620, p < 0.001), in contrast WPV showed a negative correlation with PC (r = −0.807, p = 0.005). Mediation analysis revealed that PsyCap mediated the WPV-PC relationship, accounting for 47.5% of the total effect.ConclusionNursing students exhibited moderate levels of PsyCap and PC, with the prevalence of WPV being slightly lower than reported in comparable studies. And PsyCap fully mediated the relationship between WPV and PC. These findings revealed that nursing administrators and educators should enhance and develop nursing students’ PsyCap to lower the adverse effects of WPV and promote higher levels of PC.